Mapping the area of social entrepreneurship: the social entrepreneurship scheme : working paper - Krlev, Gorgi (SSRN eLibrary, 2011)
Scholars currently discuss various concepts affecting the social sphere. One of the most prominent phenomena is the one of Social Entrepreneurship (SE). Due to the fact that definitions of the term get increasingly precise, there is less remaining confusion about the meaning of SE itself, however, many related discussions are taking place simultaneously pointing into a similar direction. Neighboring concepts covered by scholarly research include shifts in the ‘traditional’ nonprofit sector, the Social Business concept, ‘strategic Corporate Social Responsibility’ and ‘Base-of-the-Pyramid’ business. It becomes evident that we witness an increasing tendency towards hybridity that surpasses boundaries of sectors traditionally held distinct - a development regularly referred to as a ‘blurring of boundaries’ between the spheres of the state, the market and civil society. This paper aims at shedding some more light on the field of social impact activity and at putting existing concepts in relation to each other by conceptualizing a ‘Social Entrepreneurship Scheme’. The scheme shall also serve as a tool to enhance studies of ‘Social Entrepreneurial Organizations’ by offering a framework for integrating the examined entities into the larger context.